2013
DOI: 10.1186/1475-9276-12-76
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and constraints of intimate partnerships for HIV positive sex workers in Kibera, Kenya

Abstract: IntroductionResearch on the intimate partnerships of female sex workers (FSWs) tends to focus on the risks associated with these relationships. This paper takes as its starting point that the situation of FSWs is better understood by including knowledge of the benefits of their intimate partnerships. Specifically, we employ the conceptual framework provided by emergent research examining intimacy as a complex fusion of affective and instrumental dimensions among sex workers. This perspective allows us to frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…31 Fourth, we did not conduct a partner-level analysis to evaluate the frequency of IPV with different partners, including more than one index partner. 16,23 Asking about IPV committed by the current or most recent emotional partner is consistent with use of the WHO VAW tool, but could underestimate the true prevalence of IPV in the past year if women have more than one emotional partner. While our results may not be generalisable to all other populations, our findings are likely applicable to other women engaged in transactional sex.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…31 Fourth, we did not conduct a partner-level analysis to evaluate the frequency of IPV with different partners, including more than one index partner. 16,23 Asking about IPV committed by the current or most recent emotional partner is consistent with use of the WHO VAW tool, but could underestimate the true prevalence of IPV in the past year if women have more than one emotional partner. While our results may not be generalisable to all other populations, our findings are likely applicable to other women engaged in transactional sex.…”
Section: Discussionmentioning
confidence: 91%
“…16,22,23 FSWs may also experience a high frequency of IPV, which may affect their overall health and ongoing risk of unintended pregnancy and HIV transmission. 16,22,24 One cohort study of HIV-negative FSWs in Kenya reported that 55.0% of women had experienced any physical or sexual violence by an ‘emotional’ partner in the past year. 24 Limitations to the existing literature in African FSWs include a focus on violence by clients and police rather than IPV, lack of standard definitions of IPV in this population and lack of studies on the correlates of IPV in HIV-positive FSWs.…”
Section: Introductionmentioning
confidence: 99%
“…ART adherence and viral suppression was assessed in six articles (Braunstein et al, 2011; Konate et al, 2011; Benoit et al, 2013; Fielding-Miller, Mnisi, Adams, Baral, & Kennedy, 2014; Mbonye, Rutakumwa, Weiss, & Seeley, 2014; Goldenberg et al, 2016). Lack of adequate food was often linked to the difficulty of adhering to ART (Braunstein et al, 2011; Fielding-Miller et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, substance use was strongly associated with gaps in ART treatment and likelihood of a detectable viral load (Mbonye et al, 2014). One article highlighted the importance of intimate partner support for ART adherence (Benoit et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…A third possible explanation is that reporting IPV may be a marker for certain positive features of long-term partnerships (69). Our qualitative findings revealed that many women wanted to stay with their mzees , despite episodes of IPV, because of love, companionship, and financial stability.…”
Section: Discussionmentioning
confidence: 99%